Pengaruh Bauran Pemasaran Terhadap Minat Berkunjung Kembali Ke Romokalisari Adventure Land Surabaya - Adistya Pramudyana; Budi Prabowo (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine and analyze the influence of the marketing mix on the intention to revisit Romokalisari Adventure Land Surabaya, both simultaneously and partially. This study uses independent variables (X), namely "Product, Price, Place, Promotion, People, Process, and Physical evidence," and the dependent variable (Y), which is the Intention to Revisit. The research employs an associative quantitative method with purposive sampling technique, involving 100 respondents who visited Romokalisari Adventure Land Surabaya. Data collection is done through a questionnaire. Instrument testing includes validity and reliability tests, and the results indicate that the entire instrument is valid and reliable. The data analysis technique involves multiple linear regression, classic assumption tests, F-test, and t-test. The results of this study show that, partially, "Product, Price, Promotion, People, and Physical evidence" have a significant and positive influence, while Place and Process variables do not significantly affect the intention to revisit Romokalisari Adventure Land Surabaya. Simultaneously, "Product, Price, Place, Promotion, People, Process, and Physical Evidence" collectively have a significant and positive influence of 74.9% on the intention to revisit Romokalisari Adventure Land Surabaya.